The Mastery of Science Concepts in Solving Physics Problems for Junior High School Students - Silaban, Bajongga; Nainggolan, Juliper (Jurnal Pendidikan Indonesia, 2022)
The low learning absorption of students reflects the gap between the demands of the curriculum and the level of students' thinking abilities. The inability of students to do a task is not only because they do not have the necessary prerequisite knowledge, but also their limited ability to process the amount of information received. This study aims to analyze the relationship between mastery of science concepts, especially physics, on students' ability to solve physics problems. This research is an experimental research with a pre-experimental type and a one-shot case study design. The population in this study were 9th grade junior high school students. Determination of the sample was carried out by purposive sampling method, in order to obtain a sample of 48 students. Data collection was carried out using an instrument in the form of an achievement test for mastery of the concept of science (physics). Data analysis was carried out descriptively and inferentially. The results showed that the mean (average) was 77.40 and the standard deviation (sd) was 6.58, which was included in the good category, while for the physics problem solving ability test the mean (average) was 80.16, and the standard deviation (sd) was 6.28 which was also categorized as good. which can exceed the minimum completeness criterion (KKM) score above 70. The magnitude of the correlation coefficient index (r) is 0.815 (high), with a coefficient of determination (r2) of 0.6642, which indicates that at least 66.42% mastery of the concept of science (Physics) ) can contribute to students' ability to solve physics problems.